Validitas Pengembangan Media Pembelajaran Interaktif “Sikarji” pada Materi Kebudayaan Daerah Jawa Timur Siswa Kelas V - Khoirun Nisa’; Frans Aditia Wiguna; Karimatus Saidah (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study was motivated by the low level of engagement and understanding among fifth-grade students at SDN Mrican 1 regarding the Pancasila Education subject, specifically the topic of East Java regional culture. Instruction dominated by lecture methods and limited media led to student boredom, a lack of focus, and difficulty retaining information, despite the school possessing technology-based learning facilities that had not been optimally utilized. This study aimed to determine the validity of the "Sikarji" interactive learning media. Sikarji incorporates content on East Java regional culture combined with interactive features such as drag-and-drop activities and memory-matching cards designed to make learning more engaging. The study employed the Research and Development (R&D) method using the ADDIE model; however, the scope was limited to the ADD stages (Analysis, Design, and Development/Validation). Validation sheets assessed by subject matter experts and media experts served as the research instruments. The results indicated a validity score of 96% from subject matter experts and 86.6% from media experts. The average validation score reached 91.3%, placing it in the "highly valid" category. Consequently, the Sikarji interactive learning media is deemed highly valid and suitable for implementation as a learning tool to assist students in understanding East Java regional culture within the Pancasila Education curriculum.